The experimental study of pathological changes of visceral leishmaniasis in dog in Basrah province - Mahdi, Dawood Salman (University of Thi-Qar Journal of Science, 2013)
The aim of this study was to evaluate the histopathological effect of leishmaniasis on liver and spleen of  dog. Five dogs were inoculated with leishmania in laboratory to study variable histopathological change in relation to serological analysis. Section of liver and spleen were cut and stained with Leishman and haematoxylin and eosin stain for microscopical examination. Liver was show a pseudolobule, few inflammatory cells infiltration mostly lymphocytes and plasma cells and liver parenchyma is absent with a few necrotic hepatocytes with areas of fibrosis. Spleen was greatly enlarged, section of it shown few sinusoids have large numbers follicular structures,eosinophilic hyalinized wall of blood vessels ,multiple areas of necrosis and destroying the normal architecture white pulp, red pulp is largely occupied by collection ofmacrophages (histiocytes). When compared with natural dog that have negative serological test.